Personality and endogenous/major depression: an empirical approach to typus melancholicus: validation of Typus melancholicus core-properties by personality inventory scales - Mundt, Christoph; Backenstraß, Matthias; Kronmüller, Klaus-Thomas; Fiedler, Peter; Kraus, Alfred; Stanghellini, Giovanni (Psychopathology, 1997)
The purpose of this study was to objectify some of the personality dimensions of the typus melancholicus (TM) personality formation in endogenous depressives and to compare the consistency of the term used in questionnaires with the original concept as delineated in our preceding paper. The prevalence of TM in endogenous-depressive inpatients was 51% for patients with clearly salient TM features. In addition 25% of the sample showed TM features to a minor extent. These findings are consistent with the literature. MMPI and MPI could not separate TM and non-typus melancholicus (NTM) in univariate analyses. However, the Munich Personality Test (MPT) contributes to validating the TM concept. TM depressives scored significantly higher in MPT subscales rigidity and norm orientation. According to its item structure the MPT rigidity subscore can be considered to conceptually encompass hypernomia, i.e. the patient’s incapacity to change the norms that were once adopted. Based on the characteristics of item formulations in the MPT subscore norm orientation it was hypothesized that this subscore corresponds to the concept of heteronomia, i.e. conformism towards externally determined and uncritically followed social norms. Since MPT norm orientation in TM does not covariate with control scales of the other inventories used in this study, it is likely that MPT norm orientation refers to the TM patient’s sincere commitment to social norms rather than to a sham reaction in the sense of a lie scale. There was no consistent indication that TM shows lower neuroticism scores than NTM.
Gesehen am 22.01.2021